Clinical presentation of ulcerative colitis among Bangladeshi population twenty years experience from a tertiary care hospital in Bangladesh (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: The prevalence of Ulcerative colitis has been increasingly reported from Western countries as well as other Asian countries. Our personal experience shows that Ulcerative colitis is not uncommon in our country and is being diagnosed more commonly. So, there is need to study the disease pattern in our country. Objective: To find out the clinical presentation, among Bangladeshi population. Methods: A hospital (Department of Gastroenterology, Bangabandhu Sheikh Mujib Medical University) based study registering previously diagnosed and newly diagnosed cases of Ulcerative colitis, was carried out from January 1990 to June 2010. Data that were obtained are: age and sex of the patients, clinical presentations like bloody diarrhoea, per rectal bleeding, diarrhoea without per rectal bleeding, urgency, tenesmus, abdominal pain, fever, anorexia, weakness, weight loss. Data regarding physical findings and extra intestinal manifestations were also recorded. Results: Out of 164 patients 65.24% (107) were male and 34.76% (57) were female. The male- female ratio was 1.88 : 1. Mean age of male patients was 36.14(±11.66) years and mean age for female patients was 33.15(±11.12) years. Maximum number of male patients were in 21-40 years age group (65.42%, 70). Maximum number of female patients were in 21-30 years age group (42.10%, 24). Maximum number of both male and female patients were in 21-30 years age group (35.97%, 59). Clinical features of 164 patients showed that 87.28% (143) had bloody diarrhoea, 20.12% (33) had per-rectal bleeding, 4.26% (7) had diarrhoea without per rectal bleeding, 1.21% (2) had urgency, 5.48% (9) had tenesmus, 33.53% (55) had abdominal pain, 17.66% (29) had fever, 18.29% (30) had anorexia, weakness and 17.68% (29) had weight loss at their initial presentation. Physical examination of 164 patients revealed that 81(49.39%) patients had normal findings, 7 (4.27%) patients had oedema and 83 (50.61%) patients had anaemia. Extra intestinal features were absent in 143 (87.20%) patients out of 164 patients. The rest 21 (12.80%) patients had joint involvement and 2 ( 1.21 % ) patients had ocular involvement. There was no patient with skin involvement. Conclusion: The clinical presentation of Ulcerative colitis in our country is mostly similar compared to other Asian' and Western countries except higher male-female ratio, presence of oedema and wide variability of extra intestinal involvement. These differences are probably due to social and cultural reasons, poor nutritional status, incomplete workup or records and influence of various enviornmental factors. To validate these results further prospective studies are needed.